Pathogenetic Association of Digestive System Lesions with Systemic Lupus Erythematosus: Characteristics and Prevalence - Abrahamovych Уляна; Abrahamovych Орест; Nadashkevich Олег; Farmaha Марта; Kobak Любов (Psychosomatic Medicine and General Practice, 2020)
Introduction. The prevalence rate of the digestive system lesions in patients with systemic lupus erythematosus (SLE) ranges from 8.0 to 50.0%. The symptoms caused by systemic lupus erythematosus (immunocomplex inflammation, vasculitis, etc.) have not been clearly distinguished yet from those that are associated with co-occurring diseases or adverse effects of medications used to treat patients with SLE. Objective. To characterize and clarify the prevalence of the digestive system lesions that are pathogenetically associated with systemic lupus erythematosus. Materials and methods. 370 patients (331 women and 39 men), stratified by age, duration, and activity of SLE, were included in the study and subjected to comprehensive examinations. The results were processed in Microsoft Excel using descriptive statistics, χ2 test, z-test for comparisons between two proportions; the relationship was considered to be statistically significant when p < 0.05. Results. The digestive system lesions were detected in 225 (60.81%) patients with systemic lupus erythematosus. The prevalence of steatohepatitis, autoimmune hepatitis, and chronic pancreatitis rose with the progression of the underlying disease, so we concluded that they may be considered to be pathogenetically associated with systemic lupus erythematosus as syntropic comorbid lesions. Other digestive system lesions – chronic pharyngitis, cardiochalasia, gastroesophageal reflux disease, esophagitis, chronic gastritis, peptic ulcer, chronic duodenitis, duodenogastric reflux, duodenal ulcer, chronic viral hepatitis B, chronic viral hepatitis C, toxic hepatitis, liver cirrhosis, acalculous cholecystitis, chronic cholecystitis (asymptomatic gallstones, chronic calculous cholecystitis, gallbladder polyps), irritable bowel syndrome, chronic colitis, hemorrhoids, dolichosigma, peritoneal adhesions – are only comorbidities, ie. co-occurring digestive system lesions, since there was no relationship between their prevalence and the progression of the underlying disease. The mesenchymal inflammatory syndrome was detected in most patients with systemic lupus erythematosus and pathogenetically associated syntropic comorbid steatohepatitis. Hepatocellular dysfunction syndrome was detected in the three-fourths of patients with SLE and steatohepatitis. The mesenchymal inflammatory syndrome was also detected in all patients with SLE and pathogenetically associated syntropic comorbid autoimmune hepatitis. More than half of the patients with SLE and autoimmune hepatitis were also diagnosed with hepatocellular dysfunction and hepatic cytolysis syndromes. The asthenic-neurotic clinical syndrome occurred in the three-fourths of patients with SLE and pathogenetically associated syntropic comorbid chronic pancreatitis. Almost every second patient with SLE and chronic pancreatitis had a dyspeptic syndrome. Steatohepatitis was detected predominantly in patients aged 25 to 59 (young age subgroup II and middle age group). It was not detected in patients with the SLE duration of less than one year. Autoimmune hepatitis was detected predominantly in elderly patients and patients with the SLE duration of more than ten years. Chronic pancreatitis was significantly less prevalent in women and more prevalent in elderly patients – it occurred in almost half of them. It was absent in patients with the SLE duration of less than one year. Patients with the SLE duration of 6-10 years had the highest prevalence of chronic pancreatitis.